Time and Space View of Human-Water Relationship Discipline and Its Research Methods - ZUO Qiting (Renmin Zhujiang)
The research object of the human-water relationship discipline is the human-water system composed of nature and human society.It has distinct time and space properties and will inevitably encounter problems of temporal and spatial scales.Therefore,it is of great significance to study and clarify the time and space view of the human-water relationship discipline.On the basis of the previous research and common examples,this paper expounds the temporal and spatial scales of research on the human-water relationship.Then,we put forward the time and space view of the human-water relationship discipline and discuss its main arguments and application approaches.After that,we introduce the research methods of the spatiotemporal analysis of the human-water relationship, which mainly include three categories,i.e.,the time series analysis method,spatial evolution analysis method,and spatiotemporal coupling analysis method.Finally,the prospect of further research is given.The research can lay a foundation for the human-water relationship discipline to deal with problems of temporal and spatial scales and can also provide a reference for research on similar scale problems.